Correlation of human development and economic growth of the national economy - Đorđević Vladimir; Cvetković Milica; Momčilović Aleksandar (Trendovi u Poslovanju)
The area that causes great attention of economic science is the issue of growth and development. The impact of human resources on economic growth is of great importance. Human capital is the driver of the economic growth of any national economy, on the other hand, the state is the driver of education of its population. An important driver of development is education, i.e. investing in the education system, which further drives other macroeconomic variables. Both theory and practice are increasingly dealing with the issue of human capital, as important components and factors of the overall economic development of the national economy. Investments in education result in an increase in economic growth, this increase allows for greater investment in future education. Long-term economic growth determines the standard of living, which directly affects human development. The Human Development Index sublimates several parameters in itself and at the same time shows correlations between the economy, quality of life, and level of education in the country. The paper aims to point out the importance of human capital in economic science and practice through the paradigm of the concept of human development, following the trends of HDI in the Republic of Serbia and the surrounding countries.